Tragopogon porrifolius improves serum lipid profile and increases short-term satiety in rats - Zeeni, Nadine (2013)
Tragopogon porrifolius (white salsify) is an edible plant commonly used in folk medicine in Lebanon and neighbouring countries. This study investigates the effect of the aqueous extract of the aerial part of T. porrifolius on lipemia and appetite regulation using a rat model. Food intake, abdominal fat percentage, blood lipid profile, liver weight and liver enzymes were assessed following 4 weeks of extract intake via drinking water (50, 100, or 250 mg/kg body weight) in standard high-carbohydrate and high-fat dietary conditions. In a separate study, the short term effect of a preload of T. porrifolius extract on food intake was evaluated. Results showed that consumption of the plant extract for a period of four weeks resulted in a marked improvement of the lipid profile (triglycerides, total cholesterol, LDL and HDL cholesterol). Body weight, food intake and intra-abdominal fat were also lower in animals given the plant extract (100 and 250 mg/kg). In addition, T. porrifolius extract preload produced a dose dependent decrease in food intake observed over 24 h. The intake of T. porrifolius aqueous extract therefore improved lipemia and increased satiety in rats with no visible adverse effects.